COMMUNITY SERVICE EDUCATION FOR POSTPARTUM MOTHERS RELATED TO OPTIMIZING GROWTH AND DEVELOPMENT AND CHILD PROTECTION IN HIGH-RISK GROUPS IN SUB-DISTRICTS THE FIELD - Fistaqul Isnaini; Rohmatun Nazilah; Yulia Amelia (Cattleya Darmaya Fortuna, 2024)
The postpartum period is a crucial period for mothers to pay full attention to the growth and development of the baby, especially in high-risk groups that need extra supervision. Lack of understanding of growth and development stimulation and child protection is often an obstacle in achieving optimal child growth and development. This community service activity aims to increase the knowledge of postpartum mothers about growth and development stimulation strategies and the importance of child protection in Medan Tuntungan District. The program will be held on June 20, 2024 with interactive counseling methods and group discussions. The results of the evaluation showed a significant increase in participants' understanding of appropriate stimulation techniques according to the age of the baby and the importance of creating an environment that supports child protection. This education is expected to strengthen the role of mothers in optimizing children's growth and development and providing adequate protection from an early age.